Unravelling Shared Pathways Linking Metabolic Syndrome, Mild Cognitive Impairment, Dementia, and Sarcopenia - Daniela Ceccarelli Ceccarelli; Sebastiano Bruno Solerte (Metabolites)
Background: Aging is characterized by shared cellular and molecular processes, and aging-related diseases might co-exist in a cluster of comorbidities, particularly in vulnerable individuals whose phenotype meets the criteria for frailty. Whilst the multidimensional definition of frailty is still controversial, there is an increasing understanding of the common pathways linking metabolic syndrome, cognitive decline, and sarcopenia, frequent conditions in frail elderly patients. Methods: We performed a systematic search in the electronic databases Cochrane Library and PubMed and included preclinical studies, cohort and observational studies, and trials. Discussion: Metabolic syndrome markers, such as insulin resistance and the triglyceride/HDL C ratio, correlate with early cognitive impairment. Insulin resistance is a cause of synaptic dysfunction and neurodegeneration. Conversely, fasting and fasting-mimicking agents promote neuronal resilience by enhancing mitochondrial efficiency, autophagy, and neurogenesis. Proteins acting as cellular metabolic sensors, such as SIRT1, play a pivotal role in aging, neuroprotection, and metabolic health. In AD, β-amyloid accumulation and hyperphosphorylated tau in neurofibrillary tangles can cause metabolic reprogramming in brain cells, shifting from oxidative phosphorylation to aerobic glycolysis, similar to the Warburg effect in cancer. The interrelation of metabolic syndrome, sarcopenia, and cognitive decline suggests that targeting these shared metabolic pathways could mitigate all the conditions. Pharmacological interventions, including GLP-1 receptor agonists, metformin, and SIRT 1 inducers, demonstrated neuroprotective effects in animals and some preliminary clinical models. Conclusions: These findings encourage further research on the prevention and treatment of neurodegenerative diseases as well as the drug-repurposing potential of molecules currently approved for diabetes, dyslipidemia, and metabolic syndrome.